Penyuluhan Pentingnya Mengkonsumsi Makanan Bergizi Seimbang dalam Upaya Peningkatan Status Gizi Ibu Hamil - Rahmadhani, Sendy Pratiwi; Anggraini, Arie; Rahmawati, Eka (Fakultas Ilmu Kesehatan Universitas Borneo Tarakan, 2024)
Pregnant women are included in the nutrient-vulnerable group, so it is recommended to increase nutrient intake to meet the nutritional needs of mothers and fetuses, achieving the nutritional status of pregnant women in a normal state. Mother's knowledge about nutrition will affect the dishes and the quality of the food consumed. The form of implementation of this community service activity is in the form of counseling on the importance of consuming balanced nutrition to improve the nutritional status of pregnant women. The delivery of material was carried out by the lecture method using powerpoint, leaflet and table of the